IT alignment and firm performance in small manufacturing firms - Cragg, Paul; King, Malcolm; Hussin, Husnayati (Elsevier, 2002)
The concept of IT alignment has been discussed in the literature, but almost always in the context of large firms. Similarly, attempts to measure alignment and relate it to performance have been made, but primarily based on work in larger firms. This study focused on measuring the alignment of business strategy and IT strategy (ITS) among small UK manufacturing firms and then investigated the link between alignment and performance. The method built on prior studies, developing approaches to alignment used with larger firms and integrating other concepts and measures from the small firm literature. Using a mail questionnaire, data from 250 firms was collected on nine strategy areas so that business and ITS responses could be compared. IT alignment was explored using both the matching and moderation approaches. The moderation approach appeared more effective in identifying IT alignment. The results indicated that a significant proportion of small firms had achieved high IT alignment. Furthermore, the group of small firms with high IT alignment had achieved better organisational performance than firms with low IT alignment. This is consistent with findings in large firms and opens up possibilities for further study of IT alignment in small firms.